Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.3928/1081-597x-20040301-03
|View full text |Cite
|
Sign up to set email alerts
|

Eight-year Follow-up of Photorefractive Keratectomy for Myopia

Abstract: PURPOSE: We evaluated 8-year results of excimer laser photorefractive keratectomy (PRK) for myopia in terms of stability and late complications. METHODS: Ninety-two myopic eyes of 55 patients were treated with a single-step method using an Aesculap-Meditec MEL 60 excimer laser with a 5.0-mm ablation zone. Treated eyes were divided into three groups according to preoperative refraction: low myopes (≤-6.00 D), medium myopes (-6.10 to -10.00 D), and high myopes (>-10.00D). RESULTS: Change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Our results seem comparable with other long-term prospective and retrospective results 8 to 16 years after PRK. [11][12][13][14][20][21][22][23] Concerning refractive predictability and stability, Alio et al 20,21 reported 75% of eyes (with less than -6 D) and 58% of eyes (with more than -6 D) being within ±1.0 D 10 years after PRK. Bricola et al 12 reported no late regression after 14 years, and Guerin et al 11 found a mean SE error of -0.69 ± 0.79 in 23 patients after 16 years.…”
Section: Discussionmentioning
confidence: 99%
“…Our results seem comparable with other long-term prospective and retrospective results 8 to 16 years after PRK. [11][12][13][14][20][21][22][23] Concerning refractive predictability and stability, Alio et al 20,21 reported 75% of eyes (with less than -6 D) and 58% of eyes (with more than -6 D) being within ±1.0 D 10 years after PRK. Bricola et al 12 reported no late regression after 14 years, and Guerin et al 11 found a mean SE error of -0.69 ± 0.79 in 23 patients after 16 years.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported, as a common occurrence after PRK, a mean early postoperative refractive regression of Ϫ0.50 D during the fi rst year after treatment and a slow myopic regression for up to 8 years of follow-up. [14][15][16][17][18] However, aside from the role of the anterior 19 and posterior corneal curvatures, 20 the refraction of the eye optics may depend on more variables such as age-related changes of the lens and vitreous. [21][22][23] Because the laser ablation reshapes the corneal tissue that showed mechanical response to a change in its structure 24,25 and considering the expected longevity of patients undergoing refractive procedures, it is a main point of interest to investigate whether progressive remodeling of the cornea occurs in the years following refractive surgery.…”
mentioning
confidence: 99%
“…Pietilä et al . in an 8‐year retrospective follow‐up study reported good stability and minimal haze and concluded the PRK was safe for patients with myopia up to and in excess of 10 D 20 . The 12‐year follow‐up study by Rajan et al 21 .…”
Section: Resultsmentioning
confidence: 98%